The Depiction of White Savior Narrative in John Ferrely’s Green Book (2018) Movie - Dania Rachma Prabasiwi; Rifka Pratama (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2022)
In the other manifestations, racism may refer to a very implicit condition and it called as a white savior narrative by an expert. In Green Book movie directed by Peter Farrelly’s depicts this phenomenon. The writer try tries to examine white savior phenomenon depicted inside the movie where there is the dominance of Tony lip as a white people who becomes a savior for black people, Don Shirley. Library research method is used as the research method of this study; meanwhile exponential approach is applied to focus its discussion by examining several of the intrinsic elements namely setting, character, and conflict. Meanwhile extrinsic approach, especially sociological approach, which discusses the white savior phenomenon inside the movie, is used in this study. The result of this discussion shows that there exist some white savior narrative phenomena reflected by Tony Lip, one of the main characters inside the movie.  Keywords: white savior; racial discrimination; racism In the other manifestations, racism may refer to a very implicit condition and it called as a white savior narrative by an expert. In Green Book movie directed by Peter Farrelly’s depicts this phenomenon. The writer try tries to examine white savior phenomenon depicted inside the movie where there is the dominance of Tony lip as a white people who becomes a savior for black people, Don Shirley. Library research method is used as the research method of this study; meanwhile exponential approach is applied to focus its discussion by examining several of the intrinsic elements namely setting, character, and conflict. Meanwhile extrinsic approach, especially sociological approach, which discusses the white savior phenomenon inside the movie, is used in this study. The result of this discussion shows that there exist some white savior narrative phenomena reflected by Tony Lip, one of the main characters inside the movie